Antioxidant Activity and Brine Shrimp Lethality of Tragia involucrata L.Laila Impex Communication # 63. - G. SAVITHRI, MANTENA; A.S. CHANDANADEVI, BHUPATIRAJU; V. KRISHNARAJU, ALLURI; V. RAO, CHIRRAVURI; TRIMURTULU, GOLAKOTI (Asian Journal of Chemistry, 2010)
Various extracts of T. involucrata have shown superoxide free radical, DPPH radical scavenging activities and brine shrimp toxicity. Ethyl acetate and methanol extracts showed poor to moderate antioxidant activity. However the aqueous methanol extract showed potent antioxidant activity and the fractions obtained from bioactivity guided fractionation of aqueous methanol extract showed potent antioxidant activity when compared to other extracts of T. involucrata and known commercial antioxidants like BHT, BHA. Methanol and aqueous methanol extracts also showed moderate brine shrimp lethality and fractions obtained from aqueous methanol extracts showed potent brine shrimp toxicity.